The role of brand image in mediating the influence of user generated content credibility on brand trust - Ryan Fernando; Siska Fatimah; Dr. Jumadi (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the influence of user generated content (UGC) credibility on brand image and brand trust, as well as test the role of brand image as a mediating variable in Mykonos perfume products. The background of this research is based on the increasing role of social media in shaping consumer perception and trust in brands, especially through user-generated content. The research method used is a quantitative approach with a descriptive type. The research sample amounted to 120 respondents who were selected using purposive sampling techniques. Data analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method using SmartPLS 4.0 software. The results of the study show that UGC credibility has a positive and significant effect on brand image and brand trust. In addition, brand image has also been proven to have a positive and significant effect on brand trust. Other findings show that brand image is able to significantly mediate the relationship between UGC credibility and brand trust. This indicates that the credibility of user-generated content will be more effective in increasing brand trust if it first forms a positive brand image. The value of the determination coefficient shows that the model has a strong ability to explain the brand trust variable. Thus, this study confirms the importance of authentic content-based marketing strategies in building an image and trust in local brands. The practical implication of this research is the need for companies to encourage the creation of credible user content to increase competitiveness in the digital era